Integrity Violations and Corruption in Western Public Governance: Empirical Evidence and Reflection from the Netherlands. (4th March 2018) - de Graaf, Gjalt; Huberts, Leo; Strüwer, Tebbine
Abstract : How often integrity violations occur in Western governance, and the precise nature of these violations, is as yet not very clear. Data on this subject—drawn from experience in the Netherlands—are presented here. The main research question is: What is the scale of integrity violations within Dutch public governance and what is the nature of these violations? The article provides the results of research on the perceptions of 7, 315 Dutch civil servants who were surveyed on integrity violations in their work surroundings. All told, 2, 035 respondents (nearly 28%) reported suspicion(s) of integrity violations in their direct working environment in the preceding two years. A substantial proportion of respondents said that they had experienced inappropriate and ill-mannered behavior and relatively "small" violations, such as profiting at the expense of the organization (fraud, abuse of resources) through noncompliance with working-hour regulations or by abuse of the organization's resources. Integrity of governance in a Western context concerns corruption (and fraud), but there are indeed many other types of integrity violations that are prominent in the eyes of public sector employees. The moral quality of governance is thus also related to other values and norms than incorruptibility and impartiality. It seems important to incorporate this perspective into the fierce theoretical and practical debate on the corruption and integrity of governance.